2016
DOI: 10.1002/art.39626
|View full text |Cite
|
Sign up to set email alerts
|

Stopping Tumor Necrosis Factor Inhibitor Treatment in Patients With Established Rheumatoid Arthritis in Remission or With Stable Low Disease Activity: A Pragmatic Multicenter, Open‐Label Randomized Controlled Trial

Abstract: Objective. Tumor necrosis factor inhibitor (TNFi) biologic agents are an effective treatment for rheumatoid arthritis (RA). It is unclear whether patients whose disease is in remission or who have stable low disease activity need to continue use of TNFi or can stop this treatment. This study was undertaken to assess whether patients with established RA who are in remission or have stable low disease activity can effectively and safely stop their TNFi therapy.Methods. The study was designed as a pragmatic multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 32 publications
3
56
2
4
Order By: Relevance
“…Despite the constantly developing therapeutic options and an increasing shift of interest towards the management of withdrawing bDMARDs when remission is achieved [14][15][16], robust evidence is still needed on the appropriate prescription strategy of first-line bDMARD and switching strategy in real-life settings. To the best of our knowledge, this is the first study demonstrating that higher age and comorbidities influence the choice towards ABA and TCZ compared to TNFi in a large registry study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the constantly developing therapeutic options and an increasing shift of interest towards the management of withdrawing bDMARDs when remission is achieved [14][15][16], robust evidence is still needed on the appropriate prescription strategy of first-line bDMARD and switching strategy in real-life settings. To the best of our knowledge, this is the first study demonstrating that higher age and comorbidities influence the choice towards ABA and TCZ compared to TNFi in a large registry study.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable to the results of the Corrona analysis, the improvement of clinical characteristics and PROs in the trials peaked within the first year of treatment initiation, with a subsequent plateau. Although our study did not follow patients to determine outcomes after discontinuation of adalimumab therapy, other studies have shown that patients who discontinue treatment with TNF inhibitors have an increase in the number of flares and are less likely to maintain low disease activity [33,34]. It should be noted that patients enrolled in randomized clinical trials are selected because they have fewer significant comorbidities and fulfill very strict inclusion criteria, which may not reflect the real-world population.…”
Section: Discussionmentioning
confidence: 99%
“…Moghadam и соавт. [29] в открытом РКИ наблю-дали 817 больных РА (средняя длительность заболевания составляла 11 лет), у которых не менее 6 мес сохранялась ремиссия или низкая активность болезни (DAS28 <3,2). Пациенты были рандомизированны на две группы: в пер-вой проводилась поддерживающая терапия ГИБП (n=286), во второй -ГИБП отменялись (n=531).…”
Section: тоцилизумабunclassified
“…В 2013 г. был предложен индекс оценки актив-ности заболевания -Multi-Biomarkers Disease Activity (MBDA) [33,34]. Речь идет о создании коммерческого на-бора, включающего 12 биомаркеров (С-реактивный бе-лок -СРБ, эритроцитарный фактор роста, ИЛ6, лептин, ММП1, ММП3, резистин, сывороточный амилоидный бе-лок А, рецептор 1 ФНОα, сосудистую молекулу клеточной адгезии 1, фактор роста эндотелия сосудов А, хрящевой гликопротеин YKL40), который позволил бы разработать алгоритм для классификации активности РА по шкале от 0 до 100: низкая (<29), средняя (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) и высокая (>40). Позднее J. Rech и соавт.…”
Section: предик торы обостренияunclassified